A condition that should be kept in mind in incarcerated hernia: Amyand’s hernia - Bozan, Mehmet Bugra (North Clin Istanb, 2017)
As a complication of inguinal hernia, incarcerations are often seen in emergency services. Incarceration is an acute complication of inguinal hernia presenting as surgical emergency. The sac of inguinal hernia most frequently contains omentum and intestine but sometimes organs such as appendix and Meckel’s diverticulum can also be seen in the hernial sac. We present a case of Amyand’s hernia containing appendix in the incarcerated herniated sac.